Triethylenetetramine reduces some blood parameters in alloxan-induced diabetes mellitus in New Zealand white rabbit: evidence for histopathologic effects - Reza Golam Mohebbi; Kaveh Azimzadeh; Amir Amniattalab (Mazandaran University of Medical Sciences, 2016)
This study aimed to assess whether the triethylenetetramine (TETA) is impressed the plasma level of homocysteine (Hcy), total sialic acid (TSA) and cardiac troponin I (cTnI) as cardiovascular diseases risk factors, cystatin c (Cys c) and glucose along with histopathologic changes in alloxan induced diabetes mellitus in rabbit. Twenty number New Zealand white rabbits were assigned for this study. After induction of diabetes mellitus, TETA was orally administrated with different doses (10, 20, 40 mg/kg/day, A, B, C groups respectively) for 6 months daily and group D (as positive control) not received TETA. In the following, above parameters, insulin and glucose were measured in the all groups. Furthermore, histopathologic evaluation was carried out for aorta, kidney and pancreas in the all ones. Amounts of plasma cTnI, Hcy, TSA, Cys c and glucose concentrations decreased significantly (P < 0.01) in group C (40 mg/kg/day) compared with group D (positive control). In respect of insulin, normalizing of insulin occurred in group C (40 mg/kg/day) compared with group D (positive control). It is worth mentioning that during increasing of TETA dose, those levels decreased. In terms of histopathology, ameliorative and restoring effect of TETA on pancreatic beta-cells, glomeruli, renal tubules and aorta was determined in this study. The results suggested that TETA administration plays substantial role in tremendous alleviation of forenamed parameters and amelioration of beta-cells, renal glomeruli and tubules. Hence, TETA in the dose 40 mg/kg/day may utilize in the part of human diabetes mellitus management including cardiovascular, renal diseases and glucose normalizing.